(untitled) (Al-Farooq Journal of Sciences, 2026)
This research examines the tourist attractions of Sabratha, identifying the most important natural, historical, and cultural resources of this region. The study explores its unique geographical location on the coast and its rich cultural heritage, reflecting the succession of civilizations throughout history. It also discusses the potential for developing the region, focusing on infrastructure, enhancing services, and promoting tourism marketing. Furthermore, the research proposes a comprehensive strategy for protecting cultural heritage, improving services, developing human resources, and encouraging investment in the tourism sector to create new job opportunities and support economic and social development at both the local and national levels.